2021
DOI: 10.3389/fpls.2021.641849
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana E3 Ubiquitin Ligase BRIZ Functions in Abscisic Acid Response

Abstract: The ubiquitin system is essential for multiple hormone signaling pathways in plants. Here, we show that the Arabidopsis thaliana E3 ligase BRIZ, a heteromeric ligase that consists minimally of BRIZ1 and BRIZ2 proteins, functions in abscisic acid (ABA) signaling or response. briz1 and briz2 homozygous mutants either fail to germinate or emerge later than wild-type seedlings, with little cotyledon expansion or root elongation and no visible greening. Viability staining indicates that briz1 and briz2 embryos are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Our study not only represents a strategy for discovering new E3 ligases in certain biological processes, but also provides insights into the role of E3 ligases in controlling strawberry fruit ripening. Recently, it was reported that the homolog of FaBRIZ in Arabidopsis, AtBRIZ2, was capable of combining with AtBRIZ1, a close ortholog of AtBRIZ2, to form a functional ubiquitin E3 ligase complex, and regulate seed germination and seeding growth ( Hsia and Callis, 2010 ; Linden et al , 2021 ). This modulation might be achieved through the regulation of ABA signalling and response by these two BRIZ proteins ( Linden et al , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study not only represents a strategy for discovering new E3 ligases in certain biological processes, but also provides insights into the role of E3 ligases in controlling strawberry fruit ripening. Recently, it was reported that the homolog of FaBRIZ in Arabidopsis, AtBRIZ2, was capable of combining with AtBRIZ1, a close ortholog of AtBRIZ2, to form a functional ubiquitin E3 ligase complex, and regulate seed germination and seeding growth ( Hsia and Callis, 2010 ; Linden et al , 2021 ). This modulation might be achieved through the regulation of ABA signalling and response by these two BRIZ proteins ( Linden et al , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that the homolog of FaBRIZ in Arabidopsis, AtBRIZ2, was capable of combining with AtBRIZ1, a close ortholog of AtBRIZ2, to form a functional ubiquitin E3 ligase complex, and regulate seed germination and seeding growth ( Hsia and Callis, 2010 ; Linden et al , 2021 ). This modulation might be achieved through the regulation of ABA signalling and response by these two BRIZ proteins ( Linden et al , 2021 ). Considering that ABA plays a key role in the regulation of strawberry fruit ripening ( Jia et al , 2011 ), it is conceivable that FaBRIZ might regulate fruit ripening through directly or indirectly affecting the ABA pathway, although the direct targets of FaBRIZ remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc finger (ZF) proteins, with their characteristic finger-like structure [57], are ubiquitously distributed in eukaryotes and encompass several RING zinc finger proteins within Arabidopsis thaliana [58]. These ZF proteins play an instrumental role in signaling cascades and plant adaptation to adverse environmental conditions, including drought, temperature, and salinity [59].…”
Section: Other Upregulated Salt-responsive and Transcription Factor G...mentioning
confidence: 99%
“…Zinc finger proteins maintain a finger-like spatial configuration by binding to zinc ions through amino acids in the peptide chain, and are widely distributed in eukaryotes ( Han et al, 2020a ). RING zinc finger proteins have been identified in many plants, including Arabidopsis thaliana ( Linden et al, 2021 ; Liu et al, 2021 ; Van Nguyen et al, 2021 ), rice ( Oryza sativa ) ( Kim et al, 2020 ; Kim and Jang, 2021 ; Zhu et al, 2021 ), maize ( Zea mays ) ( Gao et al, 2012 ; Xia et al, 2012 ; Yang et al, 2018 ), pepper ( Capsicum annuum ) ( Liu et al, 2007 ; Joo et al, 2019a , 2020 ), wheat ( Triticum aestivum ) ( Agarwal and Khurana, 2018 ; Liu et al, 2018 ; Wang et al, 2020 ), potato ( Solanum tuberosum ) ( Guo et al, 2003 ; Ni et al, 2010 ; Qi et al, 2020 ), wild tomato ( Solanum pimpinellifolium ) ( Yang et al, 2016 ), wild Chinese grape ( Vitis pseudoreticulata ) ( Yu et al, 2013 ; Wang et al, 2017 ), soybean ( Glycine max ) ( Du et al, 2010 ; Biniek et al, 2017 ; Zhao et al, 2020 ), Brassica rapa ( Jung et al, 2013 ), tobacco ( Nicotiana benthamiana) ( Wu et al, 2014 ), and cassava ( Manihot esculenta Crantz) ( Dos Reis et al, 2012 ). RING zinc finger proteins have a characteristic RING zinc finger domain.…”
Section: Introductionmentioning
confidence: 99%